Evaluation of hematological findings in children with Down syndrome - Sarbay, Hakan (International Journal of Contemporary Pediatrics, 2018)
Background: Various hematological disorders and malignancies may be encountered with Down syndrome. In this article, hematological findings of children with Down syndrome were investigated. Methods: The hematological results of 106 Down syndrome children aged 3 months to 17 years were assessed retrospectively. The results were compared with a patient group consisting of non-DS and healthy children with a similar age range. Results: When compared with the control group, a significant difference was found between the frequencies of neutropenia, monocytosis, macrocytosis and anisocytosis. No significant difference was detected between the patients with macrocytosis and those without macrocytosis when the relation of macrocytosis with other hematological disorders was examined. On the other hand, the comparison between the groups with and without macrocytosis showed that the prevalence of acute leukemia was significantly higher in patients with Down syndrome. Conclusions: DS children with macrocytosis should be more closely monitored for myelodysplastic syndrome and acute leukemia.